Development Of Google Sites Learning Media On Solar System Material To Improve Science Literacy Of Grade VI Students - Mulya, Rachman; Suhartini, Erna; Haerani, Rosita Putri Rahmi (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2024)
Based on PISA data in 2022, Indonesian students scored an average of 383 in science, ranking 67th out of 81 countries. In addition, the use of technology-based learning media by teachers is not optimal. Therefore, it is necessary to develop more effective technology-based learning media to improve students' science literacy. The objectives of this research are (1) to know the feasibility of Google Sites, (2) to know students' responses to Google Sites, and (3) to analyse students' science literacy skills after using Google Sites. This study is a developmental study using the ADDIE model. The data collection methods used in this research were observation, interview, questionnaire and science literacy test. As data analysis techniques, quantitative data analysis and science literacy analysis were used. The findings of this study are: (1) The feasibility test of media and materials experts obtained a percentage of 90% and 86.2% in the "very feasible" category. (2) The students' responses obtained a percentage of 89.5% in the "very good" category. (3) The analysis of students' science literacy skills obtained a mean n-gain score of 0.73 in the 'High' category. It can be concluded that Google Sites learning media is feasible to be used in learning activities, and effective enough to improve the science literacy skills of students in class VI. Future research should consider examining the impact of network conditions on each student device, ensuring seamless access to the media.